PELATIHAN PENGEMBANGAN KOMPETENSI SUMBER DAYA MANUSIA DI SMK CINTA KASIH TZU CHI - Ekadjaja, Margarita; Siek, Vanesa; Runtuwene, Meily Helma; Farrenlie, Jesslyn Mirabel; Martens, Brigitta Griselda (Jurnal Serina Abdimas, 2023)
The main characteristics of competence are skills, knowledge, and attitudes which, if all of these characteristics are managed properly, will improve performance. The presence of vocational education in the current state has a significant impact on the correlation between education and the labor market. The current dilemma is that the largest number of unemployed people in Indonesia come from vocational school graduates. This becomes a gap between the competencies possessed by vocational schools and market needs. The partner in this PKM activity is the SMK Cinta Kasih Tzu Chi, which is located in the Cengkareng, West Jakarta. Based on the results, the main problem for partners is how to prepare graduates who are ready to enter the world of work with practical skills so that they can compete and have differentiation with high school graduates. The steps taken by the PKM team were analyzing problems, preparing training plans, preparing training materials, and presenting solutions faced by partners. In the next stage, the PKM team together with the coordinator school prepared the implementation of offline training on the topic of competency development for vocational high school students according to industry and business needs. The results are that SMK students know the competencies that must be possessed as human resources who are ready to work and innovate in business, besides that students are able to measure the personal competencies they already have so that they can know the strengths and weaknesses of the behavior they have. ABSTRAK Karakteristik utama dari kompetensi adalah skills, knowledges, dan attitudes yang jika semua karakteristik tersebut dikelola dengan baik akan meningkatkan kinerjanya. Kehadiran pendidikan kejuruan dalam keadaan sekarang ini membawa dampak yang signifikan pada korelasi antara pendidikan dan pasar tenaga kerja. Yang menjadi dilematis saat ini adalah jumlah pengangguran terbesar di Indonesia berasal dari lulusan SMK. Hal ini menjadi kesenjangan antara kompetensi yang dimiliki sekolah kejuruan dengan kebutuhan pasar. Mitra kegiatan PKM ini adalah SMK Cinta Kasih Tzu Chi yang berlokasi di daerah Cengkareng, Jakarta Barat. Berdasarkan hasil diskusi awal dengan mitra, maka yang menjadi permasalahan utama mitra adalah bagaimana menyiapkan lulusan yang siap memasuki dunia kerja dengan ketrampilan praktis sehingga dapat bersaing dan memiliki diferensiasi dengan lulusan SMA. Langkah-langkah yang dilakukan oleh tim PKM adalah menganalisa permasalahan, menyusun rencana pelatihan, mempersiapkan materi pelatihan, dan mempresentasikan solusi yang dihadapi mitra. Tahap selanjutnya, Tim PKM bersama koordinator dari SMK Cinta Kasih Tzu Chi mempersiapkan pelaksanaan pelatihan secara luring dengan topik Pengembangan Kompetensi Siswa SMK Sesuai Kebutuhan Industri Dan Bisnis. Hasil dari kegiatan PKM adalah siswa/i SMK mengetahui kompetensi yang harus dimiliki sebagai sumber daya manusia yang siap untuk bekerja dan berinovasi berbisnis, selain itu siswa mampu mengukur kompetensi pribadi yang telah dimilikinya sehingga dapat diketahui kekuatan dan kelemahan dari perilaku yang telah dimilikinya.